Study of Economic Potential and Economic Development Strategies in Bone Bolango Regency - Nilasari, Iva; Prawira, Bagus Yudha; Busnetty, Ida (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This research seeks to ascertain the economic potential of Bone Bolango Regency and provide an appropriate development plan for economic advancement. This research utilizes the Gross Regional Domestic Product (GRDP) of Bone Bolango Regency and Gorontalo Province from 2019 to 2023, using the analyses of Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Shift Share. This study's findings suggest that Bone Bolango Regency has a viable economic sector for development, characterized as a base sector with promising potential and a superior competitive advantage, namely in the Mining and Quarrying sector, as well as the Construction sector. The method used to enhance economic growth in Bone Bolango Regency involves industrial development that emphasizes key industries with promise.